Hemangioma treated with sclerosing solution (sodium tetradecyl-sotradecol) - Gervasio, Natividad C.
Management of hemangiomas is multivactorial in nature. Age of patient, location, and size of the lesions are of primary considerations. The decision as to the choice of treatment modalities ranges from non-surgical to surgical.
This paper will presetn two cases involving female, both 2 years of age. Case No. 1 manifested a mass on the 43 and 55 completely covering those teeth that bled on slight provocation and diagnosed as heman-gioma on biopsy. Case No. 2 presented a swelling of the gum at the lower right 84 & 85 twice diagnoesd as "Granulating tissue with psedoepitheliomatus hyperplasia". This was later revealed as "Hemangioma."
The above cases were both treated with "Sclerosing Solution (Sodium Tetradecyl-Sotradecol)". The solution was administered thtorugh a series of injections under local anesthesia. Both patients did not need hospitalization and loss of blood was not need hospitalization and loss of blood was not a problem. Both patients did not experience any untoward reactions and continuous follow-ups still being done after 3 months, 6 months, and a year after termination of treatment. Treatment was pronounced favorable and successful.
Keywords: Hemangiomas; Sodium Tetradecyl-Soltradecol.